Substrate Stiffness Influences the Time Dependence of CTGF Protein Expression in Müller Cells - Joshua, T Davis; William, J Foster (International Physiology Journal, 2018)
Following ocular trauma and retinal detachment, gliotic changes in the retina may develop over the subsequent month, a process known as PVR (proliferative vitreoretinopathy). There have been no successful therapeutic interventions to inhibit PVR. The protein CTGF (Connective Tissue Growth Factor) has been associated with retinal PVR and other fibrotic diseases of the retina in clinical studies but the mechanistic link between different pathologies and retinal gliosis has not been determined. In addition, CTGF has been previously noted to be associated, in some cases, with YAP/TAZ (Yes-associated protein and Tafazzin protein complex), transcriptional regulatory proteins that change subcellular localization in response to mechanical cues, such as the stiffness of the underlying material. We have previously shown that the mRNA for CTGF is markedly (100-fold) upregulated in retinal Müller cells grown on soft substrates. In order to evaluate if the mechanism by which mechanotransduction modulating CTGF production in retinal Müller cells involves the YAP/TAZ complex, this study tests the influence of substrate stiffness on the time dependence of CTGF protein expression, as well as subcellular localization of YAP/TAZ using a conditionally-immortalized mouse retinal Müller cell line plated on laminin-coated, polyacrylamide substrates of varying elastic modulus. Changes were assayed using immunohistochemistry and ELISA (Enzyme-Linked ImmunoSorbent Assay). In retinal Müller cells, the relationship between elastic modulus and the pattern of CTGF protein expression was bimodal, with CTGF levels rising more rapidly for cells on hard substrates and more slowly for cells grown on soft substrates. In addition, nuclear localization of YAP/TAZ corresponded directly to the maximum CTGF expression.
Keywords: Connective Tissue Growth Factor; CTGF; mechanotransduction; Proliferative Vitreoretinopathy; Müller cell; YAP/TAZ